Communication does matter: a literature review approach on integration in the NPD process. (2017) - Fotiadis, Thomas
Integration has been the subject of extensive research, due to its central role as a critical factor for success in the launching of new/innovative technological products. The intense research activity – particularly with respect to its application in the marketing and R&D departments of high-tech companies – is inferred principally as the result of the turbulent and volatile environment and as a chain-reaction of the very demanding conditions that characterise the sector. This article assumes a literature review approach which, in a compact yet fairly integrated manner, delimits the concept of integration and describes the framework of the sector's idiosyncrasies in order to provide the necessary conceptual building stones that comprise the models – frameworks developed and adopted so far and their respective implications, regarding the integration of the two key functional departments – marketing and R&D.